2019
DOI: 10.1016/j.redox.2018.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Diphthamide affects selenoprotein expression: Diphthamide deficiency reduces selenocysteine incorporation, decreases selenite sensitivity and pre-disposes to oxidative stress

Abstract: The diphthamide modification of translation elongation factor 2 is highly conserved in eukaryotes and archaebacteria. Nevertheless, cells lacking diphthamide can carry out protein synthesis and are viable. We have analyzed the phenotypes of diphthamide deficient cells and found that diphthamide deficiency reduces selenocysteine incorporation into selenoproteins. Additional phenotypes resulting from diphthamide deficiency include altered tRNA-synthetase and selenoprotein transcript levels, hypersensitivity to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 67 publications
(105 reference statements)
0
14
0
Order By: Relevance
“…Diphthamide is a unique post-translationally modified histidine at position 715 in human EF2, believed to play a role in translational fidelity (especially for proteins containing selenocysteine) [ 48 ]. Biosynthesis of diphthamide involves seven genes, DPH1-7 [ 49 ].…”
Section: Inhibition Of Protein Synthesis (Step 3)mentioning
confidence: 99%
“…Diphthamide is a unique post-translationally modified histidine at position 715 in human EF2, believed to play a role in translational fidelity (especially for proteins containing selenocysteine) [ 48 ]. Biosynthesis of diphthamide involves seven genes, DPH1-7 [ 49 ].…”
Section: Inhibition Of Protein Synthesis (Step 3)mentioning
confidence: 99%
“…In human cells, diphthamide may modulate translational decisions at paused ribosomes (stall vs. continuation vs. termination). In line with that, loss of diphthamide influences the expression levels of tRNA aminoacyl synthetases and importantly, affects the expression of selenoproteins via reduced selenocysteine incorporation at recoded SECIS-UGA codons [ 7 ]. Diphthamide deficiency also correlates with preinduction of stress pathways and gene signatures in mammalian cells, including those associated with oxidative stress responses [ 7 ] and nuclear factor of kappa light polypeptide gene enhancer in B cells (NF-κB)—transcript signatures and tumor necrosis factor-mediated pathways [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This not only reveals a novel function of Miz1, but also provides critical insights into understanding the regulation of diphthamide biosynthesis ( S1 Fig ). Thus, Miz1 would also be likely essential to the established roles of diphthamide in ensuring the fidelity of mRNA translation, maintaining cellular fitness and adaptation to various stresses [ 12 , 13 17 ]. Similar as other Dph gene KO cells [ 5 , 6 , 12 ], the Miz1-KO cells generated in this study do not exhibit obvious proliferative defects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we and others have shown that diphthamide modification plays a critical role in maintaining eEF2 in an appropriate conformation to assure fidelity of mRNA translation, as well as for maintaining full activity for protein synthesis [12,13]. Therefore, diphthamide is crucial in maintaining cell fitness and responsiveness to a variety of cellular stresses, including oxidative stress [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%